Das plantas medicinais aos fitofármacos - Devienne, K. F. [UNESP]; Raddi, G. [UNESP]; Pozetti, G. L. [UNESP] (My University, 2004)
The plants, since the antiquity, have been a resource within reach of the human being. Along millenniums, the man empirically deepened its knowledge for the improvement in the alimentation and cure conditions of its illnesses, demonstrating a narrow relation between plant use and its own evolution. A lot of people described the herbs utilization like medication form in their records and manuscripts, but many centuries have been passed until the true power of the plants was recognized. The great discoveries of the active plants principles only were possible after technological advances for the isolation and structural elucidation. Several active substances with pharmacological activity, many times indicated by the popular use, were going proved scientifically. Nowadays, the man still seeks solutions for several diseases and health problems and maybe the plants can contribute of more significant way for resolve them.
From medicinal plants to phytopharmaceuticals
Keywords: History; Medicinal plants; Phytopharmaceuticals; drug activity; drug use; herbal medicine; medicinal plant; phytochemistry